Effect of Dipping Time and Weight Loss of Fresh-Cut Apple using Polysaccharide Composite Edible Coating - Iranati Md. Sharif, Zatul; Jai, Junaidah; Fatin Alia Mustapha, Nurul; Subuki, Istikamah; Mohd. Yusof, Noorsuhana; Adawiyah Abdol Aziz, Rabiatul (International Journal of Engineering and Technology, 2018)
Composite edible coatings were made up of cassava starch and carboxymethyl cellulose (CMC) incorporated with turmeric oil (TO) as an antioxidation agent. Gas chromatography-mass spectroscopy (GC-MS) analysis was done to determine the present of secondary metabolite compounds which will act as the antioxidation agent. Fourier Transform Infrared (FTIR) spectroscopy analysis results showed that the functional group in turmeric oil that acts as an active compound was present in the edible coating film. Surface tension and wettability analyses were done to determine the right amount of starch. The best formulated edible coating formulation was S2 that was in the range of the general rule of surface tension and spreading coefficient was near to zero (-20.70 Â± 30.76 dyne/cm). The characterization on the effect of dipping time and turmeric oil towards weight loss of fresh-cut apple gave results that 180 s dipping time with 175 ppm of turmeric oil concentration had the lowest weight loss value.Â Â